Exercise for the elderly - Kongpetch, Chadaporn (Thai Journal of Nursing, 2020)
Exercise has much benefits for the elderly that it should be a part of everyday life. There are four types of exercises for the elderly including endurance, balance, strengthening, and flexibility. Endurance or aerobic exercise activities increase breathing and heart rate, brisk walking is the best advantage among aerobic exercise activities for older adults. Balance exercise help to improve mobility and can prevent falls. Strengthening or resistance exercise make the muscles stronger. Lifting weights can build up strength. Flexibility or stretching exercise stretch your muscles and help your body do daily activity and improve range of motion. Dance, yoga, and stretching are the a typical type of muscle group exercise.